Penandatanganan Akta Notariil Diluar Kantor Notaris Yang Masuk Dalam Lingkup Wilayah Jabatannya - Andika Putra Eskanugraha (Faculty of Law, University of Jember, Indonesia, 2020)
The notary has a domicile, namely the regency / city where the office is located covering area within a province from his domicile. This authority is limited by the prohibition of a notary to conduct their duties outside of the covering area. The signing of a notarial deed outside of the office is not prohibited by the Notary Law as long as it is within the scope of the domicile and the territory of the office (covering areas). The notarial code of ethics requires notaries to perform the notarial position in their offices, except for certain reasons. These reasons are not further elaborated in the code of ethics and there is no normalization of articles in the Notary Law which regulates this specific matter. Therefore, because of this, it is necessary to normalize articles in the laws and regulations to regulate the procedures for signing notarial deeds in order to maintain the values and dignity of the notary profession. This is due to notaries are officials who support the business climate by providing fast services in term of the deed preparation, providing legal certainty and signing notarial deeds that can be performed outside of their offices but still maintaining the values of the notary as an official not a deed trader.